Local Newspapers Coverage of Rural Development Issues a Decade into the Fourth Republic: A Content Analysis of the Tide and Port Harcourt Telegraph Newspapers - Iniamagha, Ikiemoye (Journal of Advanced Research in Journalism & Mass Communication, 2019)
This study set out to detect the amount of attention given to rural development issues by Local Newspapers after Nigeria returned from a long spell of military dictatorship to democratic rule in 1999. It also determined the frequency and rate of coverage of the rural development issues by local newspapers using the method. The assessment was for a period of six months, January to June 2009, ten years into the fourth republic, and the Tide and Port Harcourt Telegraph newspapers were content analysed. A sample size of 48 copies of both newspapers was studied, (that is 25% of 192) and the random fraction was ¼. The content analysis method was used in collecting data. The data was presented in simple tables of frequency distribution and percentages. An analysis of the data showed that though the Tide covered more rural development issues than the Port Harcourt Telegraph, their total performance towards the coverage of rural development issues was poor. The paper recommended among other things that local newspapers should increase their reportage of rural development issues through their features and editorials. How to cite this article: Iniamagha I. Local Newspapers Coverage of Rural Development Issues a Decade into the Fourth Republic: A Content Analysis of the Tide and Port Harcourt Telegraph Newspapers. J Adv Res Jrnl Mass Comm 2019; 6(4): 1-10 DOI: https://doi.org/10.24321/2395.3810.201908